China's Foreign Policy Think Tanks: Changing Roles and Structural Conditions - Pascal Abb (German Institute of Global and Area Studies (GIGA), 2013)
This paper provides an overview of the landscape of Chinese foreign policy think tanks, classifies them according to the activities they pursue, and offers some explanations as to how they have developed their particular characteristics - both at the level of individual institutes as well as in the broader national context. To this end, the paper introduces a new typology for the classification of think tanks and takes an in-depth look at their current activities.
Keywords: 300; think tanks; China; Chinese foreign policy; institutions; policymaking; intellectuals